Analisis Penentuan Konstanta Pengendali PID Menggunakan Garis Singgung Metode Ziegler-Nichols I pada Kurva Tanggapan Keluaran Plant - Salamena, Vicky (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2020)
The purpose of this study is to determine the PID controller constant using the Ziegler-Nichols type 1 method. This method applies the tangent-line position to the plant response curve to obtain the PID time constant which then obtains the PID controller constants.To get tangents line, a simulation of plant output responses in the matlab program is performed, from the output response curves plotted coordinate points ranging from 10% to 90% steady-state conditions in order to obtain the time and amplitude pair [x; y]. The coordinate pairs taken were 40% -60%, 30-70%, 20% -80% and 10% -90% steady-state conditions with the coordinat pair passing 50% coordinates of steady-state conditions.PID controller output response results to the constant excitation DC motor plant and AVR plant has a stable output response, control of the rise-time constant excitation DC motor and settling-time decreases so as to accelerate the plant to steady-state conditions, control of the AVR accelerates the plant reaches steady-state and decreases the amplitude of the overshoot and then oscillation period, and the best tangent-line coordinates for the PID controller output response are 20% -80%.